On a possibility of the blocking of DNA specific recognition sites by hydrogen peroxide molecules during ion beam therapy - Zdorevskyi, O.O.; Piatnytskyi, D.V.; Volkov, S.N. (Reports of the National Academy of Sciences of Ukraine, 2019)
Ion beam therapy is one of the most effective methods in treatment of cancer diseases. But up to nowadays, the mechanism of action of heavy ions on cancer cells has not been determined yet. Study of water fragmentation processes during ion beam therapy shows that, among different oxygen species, the significant amount of hydrogen peroxide molecules (H2O2) occurs in the сell medium. In the present work, the competitive interaction of H2O2 and H2O molecules with specific DNA recognition sites is studied. Interaction energies of complexes consisting of nucleic bases (adenine, thymine, guanine, and cytosine) together with hydrogen peroxide and water molecules are calculated, using the method of atom-atom potential functions and density functional theory. The atomic groups of nuc leic bases that are more energetically favorable to be bound by hydrogen peroxide rather than by water molecule are found. Formation of such complexes can block the process of DNA replication on different stages and can be one of the mechanisms of ion beam action on cancer cells.